Extending Jenkins : get a complete walkthrough of the many interfaces available in Jenkins with the help of real-world examples to take you to the next level - Simpson, Donald (Birmingham, UK : Packt Publishing, 2015)
Annotation Get a complete walkthrough of the many interfaces available in Jenkins with the help of real-world examples to take you to the next level with JenkinsAbout This Book Find out how to interact with Jenkins from within Eclipse, NetBeans, and IntelliJ IDEA Develop custom solutions that act upon Jenkins information in real time A step-by-step, practical guide to help you learn about extension points in existing plugins and how to build your own pluginWho This Book Is ForThis book is aimed primarily at developers and administrators who are interested in taking their interaction and usage of Jenkins to the next level. The book assumes you have a working knowledge of Jenkins and programming in general, and an interest in learning about the different approaches to customizing and extending Jenkins so it fits your requirements and your environment perfectly. What You Will Learn Retrieve and act upon Jenkins information in real time Find out how to interact with Jenkins through a variety of IDEs Develop your own Form and Input validation and customization Explore how Extension points work, and develop your own Jenkins plugin See how to use the Jenkins API and command-line interface Get to know how to remotely update your Jenkins configuration Design and develop your own Information Radiator Discover how Jenkins customization can help improve quality and reduce costsIn DetailJenkins CI is the leading open source continuous integration server. It is written in Java and has a wealth of plugins to support the building and testing of virtually any project. Jenkins supports multiple Software Configuration Management tools such as Git, Subversion, and Mercurial. This book explores and explains the many extension points and customizations that Jenkins offers its users, and teaches you how to develop your own Jenkins extensions and plugins. First, you will learn how to adapt Jenkins and leverage its abilities to empower DevOps, Continuous Integration, Continuous Deployment, and Agile projects. Next, you will find out how to reduce the cost of modern software development, increase the quality of deliveries, and thereby reduce the time to market. We will also teach you how to create your own custom plugins using Extension points. Finally, we will show you how to combine everything you learned over the course of the book into one real-world scenario. Style and approach Extending Jenkins explores and explains advanced Jenkins functionality from a practical point of view, teaching you real-world skills that will help you get more from this powerful software. Each key topic is explained clearly with a practical example, and in sufficient detail so you understand the concepts and can then develop your own solutions using your preferred software and languages.
The Jenkins Logger ConsoleSummary; Chapter 9: Putting Things Together; The Jenkins script console and Groovy; Groovy and Gradle as alternatives; Jenkins and Docker; Docker in Jenkins; Jenkins in Docker; Jenkins and Android; Jenkins and iOS; Keeping your Jenkins version and plugins up to date; Summary; Index.
Online resource; title from cover (Safari, viewed January 18, 2016).
Includes index.
Keywords: Jenkins (Software development tool); Jenkins (Software development tool); Computer software -- Quality control; Computer software -- Testing; Computer software -- Reliability; COMPUTER SCIENCE -- General; Computer software -- Quality control; Computer software -- Reliability; Computer software -- Testing; Electronic books; Electronic books